Racial and neighborhood disparities in mortality among hospitalized COVID-19 patients in the United States: An analysis of the CDC case surveillance database. - Atarere Joseph; Tarsicio Uribe-Leitz; Tanujit Dey; Joaquim Havens; Zara Cooper; Nakul Raykar (Public Library of Science (PLoS), 2022)
Background Black and Hispanic populations have higher overall COVID-19 infection and mortality odds compared to Whites. Some state-wide studies conducted in the early months of the pandemic found no in-hospital racial disparities in mortality. Methods We performed chi-square and logistic regression analyses on the CDC COVID-19 Case Surveillance Restricted Database. The primary outcome of the study was all-cause in-hospital mortality. The primary exposures were racial group (White, Black, Hispanic and Others) and neighborhood type (low vulnerability, moderate vulnerability, high vulnerability, very high vulnerability). Findings The overall unadjusted mortality rate was 33% and was lowest among Hispanics. In the fully adjusted models, Blacks and Hispanics had higher overall odds of dying [OR of 1.20 (95% CI 1.15, 1.25) and 1.23 (95% CI 1.17, 1.28) respectively] compared with White patients, and patients from neighborhoods with very high vulnerability had the highest mortality odds in the Northeast, Midwest and overall [Adjusted OR 2.08 (95% CI 1.91, 2.26)]. In the Midwest, Blacks and Hispanics had higher odds of mortality compared with Whites, but this was not observed in other regions. Interpretation Among hospitalized COVID-19 patients, Blacks and Hispanics were more likely to die compared to Whites in the Midwest. Patients from highly vulnerable neighborhoods also had the highest likelihood of death in the Northeast and Midwest. These results raise important questions on our efforts to curb healthcare disparities and structural racism in the healthcare setting.